Pengaruh Islamic Product Quality, Islamic Promotion dan Islamic Branding terhadap Minat Beli Konsumen pada Produk Sambal Mr. Crispy di Shop Tokopedia - Abila, Ahbab; Mukhsin, Moh.; Najmudin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this research is to determine whether Islamic product quality, Islamic promotion, and Islamic branding have an effect on consumer purchasing interest for Mr. Crispy products on Tokopedia. This study employs a quantitative method, with data collected through a questionnaire from 97 respondents, followed by multiple linear regression analysis. The results of this study indicate that Islamic product quality has a negative and significant effect on consumer purchasing interest with a t-value of (-4.583) > t-table value (1.661). Islamic promotion has a positive and significant effect on consumer purchasing interest with a t-value of (2.394) > t-table value (1.661), and Islamic branding has a positive and significant effect on consumer purchasing interest with a t-value of (6.909) > t-table value (1.661). Furthermore, Islamic product quality, Islamic promotion, and Islamic branding collectively have an effect on consumer purchasing interest with an f-value of (38.875) > f-table value (2.70).